“Work without future”: Neoliberal precarity, horizons of worthy living and generational dispossession in the Portuguese call center sector - Matos, P. A. de (Labor precarity, social exploitation, and trade union engagement: Critical approaches to work from Spain and Portugal, 2025)
Since the mid-2000s, call center employment has gradually gained prominence in the public sphere in Portugal. While little was known about what the work actually entailed or how it was performed, there seemed to be little doubt regarding who was employed by these new factories of communication characteristic of late capitalist societies (Fernie and Metcalf 1998; Buscatto 2002). The media began characterizing the call center workforce as the “500-euro generation” (“geração 500 euros”)—a publicly sanctioned label used to designate highly qualified young adults engaged in low-paid, precarious, unprotected and socially marginalized forms of service work. Snapshots of call center work began emerging regularly in the media, with the call center environment frequently portrayed as endless rows of tiny cubicles in which workers endured the drudgery of repetitive and monotonous telephone conversations with angry and abusive clients, all while subject to invasive technological surveillance, discipline, and control. In 2011, the “500/euro generation” was renamed the “troubled generation” (geração á rasca), an expression coined during a massive collective mobilization called by a group of young activists protesting the intensification of neoliberal labor precarity resulting from austerity measures. In their manifesto, activists called for participation from a coalition of the precarious population: the unemployed, “500-Eurists” and other underpaid workers, temporary workers, fraudulently self-employed workers, trainees, scholarship holders, and working students, among others. These groups aired collective grievances regarding their subjection to precarity, while identifying the irony in their position as “the highest qualified generation in the history of our country.” Even today, for ordinary people, academics, politicians, and social activists, call center work remains a striking symbol of labor precarity, a condition particularly associated with the generational disenchantment in the neoliberal idea that “each generation does better than its predecessor” (Comaroff and Comaroff 2001, 17)....